A Study on the Problems and Improvement Measures of the Regulations on Succession of Rights to Obtain Patents Prior to Patent Application - Myungsoo Kang (Journal of Intellectual Property)
Visual media platforms are expanding, and providing global access to content with just an internet connection. As video services become unrestricted by time, location, and borders, the issue of sync licenses for music used in videos has re-emerged in the video and music copyright markets. Contract issues, once considered a matter of local practice, now extend across national boundaries. This study examines the nature of sync licenses under copyright law. It aims to define the concept, identify the ownership rights involved, interpret how economic and moral rights apply, and determine who can exercise these rights. Moreover, ensuring appropriate protection for both music industry rights holders and visual media users is a key challenge in copyright law. Hence, this study also identifies the problems faced in sync licenses, explores how academia and industry can respond, and examines industry-specific issues. This investigation is valuable as Sync licenses are not just domestic issues. As new technologies develop and the environment changes, continuously reviewing and reflecting on whether the objectives and balance of copyright law are being achieved is essential.